Challenges and Opportunities for the Formulation of Madrasah Education Development Planning Management Strategies - Fernadi, Muhammad Feri; Patimah, Siti; Murtafiah, Nurul Hidayati (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
The purpose of this research is to analyze the practice of formulating planning management strategies, identify the challenges faced, and examine opportunities that can be utilized in the development of madrasah education. This study uses a type of field research with a multi-site qualitative approach. Data were obtained through in-depth interviews, observations, and documentation studies. Data sources include madrasah heads, deputy madrasah heads, teachers, education staff, and foundation managers. The research locations were conducted at MTs Al Ikhlas Tanjung Bintang, MTs Negeri 1 South Lampung, and MTs Muhammadiyah Natar. Data collection techniques include interviews, observations, and documentation, while data analysis is carried out through data reduction, data presentation, and the drawing of conclusions. The results of the study show that the formulation of planning management strategies in madrasas has been carried out through formal planning documents, such as RKJM and RKT; however, the practice is contextual in accordance with the institutional character. The main challenges include limited human resources, inadequate infrastructure and technology, insufficient funding, internal coordination issues, and weak planning and evaluation. Meanwhile, opportunities to strengthen planning arise from the development of collaborative practices, stakeholder involvement, technology utilization, innovation, and continuous evaluation, as well as the exchange of good practices between madrasas. This study concludes that the management strategy for developing madrasah education needs to be developed in an adaptive, collaborative, and institutionally context-based manner to improve the quality of education sustainably.